Does Relationship Counselling for One Work? An Effectiveness Study of Routine Relationship Counselling Services Where Only One Individual Attends. Issue 3 (10th August 2021) - Lohan, Aditi; Cao, Yuan; Petch, Jemima; Murray, Jennifer; Howe, Elizabeth
Abstract : There are no published studies investigating the effectiveness of relationship counselling (RC) where only one individual attends (individual relationship counselling (IRC)), in improving client psychological distress (PD). This is important to investigate considering the high prevalence of PD in this client group and the potential for its negative effects to cascade into other domains of an individual's life. The current study aims to address this gap by investigating the short‐term effectiveness of IRC on PD. This study further builds on previous research by investigating variables that may explain changes in counselling outcomes, including client demographics, interpersonal factors, and therapeutic factors. Data were collected from a national sample of 273 individuals presenting for RC at an Australian not‐for‐profit organisation. Results from multilevel modelling showed a significant reduction in PD over time with moderate effect size. Further, relationship status, family functioning, and the Task subscale of the Working Alliance Inventory emerged as significant predictors of PD. The results of this study have important implications for routine practice in informing opportunities to target these key variables as an avenue to increasing the effectiveness of IRC.